Implementasi budaya kerja “SEMANAK” di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Kabupaten Karanganyar - Dhiki Setiawan; Susantiningrum Susantiningrum; Tutik Susilowati (Journal of Management and Creative Business, 2023)
This research aims to determine: (1) the meaning of Semanak work culture for employees at the DPMPTSP Karanganyar Regency, (2) implementation of Semanak work culture, (3) impact, and (4) efforts to optimize the implementation of Semanak work culture. This research is a descriptive qualitative research with a phenomenological approach. Data sources are informants, documents, and observation results. The sampling technique was purposive sampling and snowball sampling. Data collection techniques using interviews, observation, and document analysis. The credibility test uses triangulation of sources and techniques, transferability, dependability, and confirmability tests. Data analysis using Miles and Huberman interactive analysis. Research results: (1) the meaning of work culture for employees: (a) guide work, (b) encourage work, (c) foster cohesiveness, (d) provide a sense of identify, and (e) generate self-commitment. (2) implementation of work culture: (a) DPMPTSP does not yet have a special work culture team, (b) leadership commitment in the form of full contribution such as installing banners and making marches, (c) tangible forms such as discipline, responsibility, communication skills, motivation, cooperation, innovation, creativity, wholehearted service, and non-discrimination (d) monitoring and evaluation of work culture does not yet exist. (3) Impact: (a) increasing employee motivation, (b) creating a good office reputation, (c) meeting good service standards, (d) realizing a conducive work environment. (4) There has been no special effort to optimize the implementation of Semanak's work culture.